Aproximações e distanciamento da percepção de técnicos e supervisores pedagógicos sobre o estilo de liderança em uma escola estadual do Rio Grande do Norte - Nascimento, Fabrício Santos do (Universidade Federal Rural do Semi-Árido, 2018)
Leadership has become a major factor for organizations of all kinds, including schools. The profile of leadership, both in schools and in other types of organizations, interferes in the work of employees, however the activities of organizational subjects can be affected in a differentiated way, because the type of place that occupies in the bureaucratic and social structure of the organization, as well as the individual expectations can generate different perceptions about the forms of leadership performance. This study aims to analyze if there are differences in the perception of professionals in the pedagogical and administrative sectors, regarding the style of leadership practiced by the director of a school in the interior of Rio Grande do Norte. In order to reach the proposed objective, a qualitative research was chosen. Data were collected through a semi structured interview with five school employees who answered directly to the school director, two from the pedagogical sector and three from the administrative sector. Through the analysis of the results, it was verified that the interviewees share the same vision about some aspects of the position adopted by the director in the school leadership, such as the monitoring of the teachers activities, the relationship with the students and the way in which they deal with the internal conflicts, however, it was observed that according to the interviewees' perceptions, the predominant leadership styles in the two sectors present differences, since while in the pedagogical sector, the leading democratic styles and educational leader prevail in the administrative sector the leading autocratic styles, technical leader and educational leader.
Monografia
Keywords: Liderança; Estilo de liderança; Liderança escolar; Leadership; Leadership style; School leadership; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO